Oil Tax Revenue and Infrastructural Development: The Nigerian Context - Y, Anewe Paulinus; Onwe, Ogbu, Moses (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The study investigated oil tax revenue and infrastructural development in Nigeria. Specifically, the study investigated the relationship between oil tax revenue and road construction, education facilities and healthcare facilities in Nigeria. The study adopted ex-post-factor research design. The population of this study was the entire Nigerian economy where the properties of data used for this research were extracted covering 1981 to 2022. A sample is a part or unit of the population. Using judgmental sampling technique, a sample of 42years’ period from 1981 to 2022 was used. Time series secondary data obtained basically from the CBN bulletin for a period of 42years (1981 to 2022) were used. Simple linear regression analysis was used to test the hypothesis on the strength of relationship between the predictor and criterion variables (Road construction, healthcare facilities, and education facilities). Co-integration test was used to determine the long-run effect of the predictor on the criterion variables (Road construction, health facilities, and education facilities). The study further suggested that Policymakers should implement transparent mechanisms to ensure efficient allocation and utilization of oil tax revenue for infrastructure projects, with regular monitoring and evaluation to track progress. Policymakers should also focus on diversifying revenue sources beyond oil taxes to reduce dependency on oil-related fluctuations and ensure a stable funding base for infrastructure development.